Pengaruh Pemberian Massase Punggung terhadap Penurunan Skala Nyeri pada Pasien Post Appendiktomi Rumah Sakit X - Fenenturuma, Bernardina Antonia; Yovita, Yovita (Jurnal Kesmas Asclepius, 2025)
The purpose of this case study is to determine the effect of back massage therapy on reducing pain scale in post-appendectomy patients at Hospital X. The method used is a case study with nursing intervention in the form of back massage in two post-appendectomy patients. The results and conclusions of the observations indicate that back massage therapy can be given to patients with mild pain scale, and is not effective for patients with severe pain. This therapy is successful in patients with moderate and mild pain scale, which is characterized by feelings of relaxation and comfort felt by the patient. Based on the research results, it can be concluded that to reduce pain in post-appendectomy patients, in addition to using back massage, pharmacological therapy also needs to be applied. This has proven effective in reducing pain, as seen in the evaluation of Ms. S and Ms. A. Keywords: Appendicitis, Back Massage, Pain.